Relational Police Work: how Police Officers Work With, On and Through ‘Personal Relationships’ in a Danish Gang Exit Programme - Johansen, Mette-Louise (The British journal of criminology, 2024)
This article examines how police-assisted gang desistance in Denmark is run on the backdrop of a particular kind of ‘relational work’ that focuses on relationships as the basis for change. The analysis is based on ethnographic fieldwork and interviews conducted in 2020 with police officers, social workers and gang defectors attached to the city of Aarhus Exit Unit, part of Denmark’s national gang exit programme. The Exit Unit’s relational work consisted of creating close, personal relationships with defectors, which could serve as a vehicle for interventions into the defectors’ relationships with gangs, family, friends and neighbourhoods. This relational work was highly ambiguous; it entailed dual practices of correctional control and help to reposition defectors in-between criminal and non-criminal social worlds.